Development Research at High Geographic Resolution : An Analysis of Night Lights, Firms, and Poverty in India Using the SHRUG Open Data Platform - Asher, Sam; Lunt, Tobias; Matsuura, Ryu; Novosad, Paul (World Bank, Washington, DC, 2021)
The SHRUG is an open data platform describing multidimensional socioeconomic development across 600,000 villages and towns in India. This paper presents three illustrative analyses only possible with high-resolution data. First, it confirms that nighttime lights are highly significant proxies for population, employment, per-capita consumption, and electrification at very local levels. However, elasticities between night lights and these variables are far lower in time series than in cross section, and vary widely across context and level of aggregation. Next, this study shows that the distribution of manufacturing employment across villages follows a power law: the majority of rural Indians have considerably less access to manufacturing employment than is suggested by aggregate data. Third, a poverty mapping exercise explores local heterogeneity in living standards and estimates the potential targeting improvement from allocating programs at the village- rather than at the district-level. The SHRUG can serve as a model for open high-resolution data in developing countries.